Jonah - Stone, Louis, 1871-1935 (Salt Lake City, UT : Project Gutenberg, 2003)
"Jonah" by Louis Stone is a novel published in 1911. Set in the slums of Sydney, it follows Jonah, a hunchback larrikin who leads a street gang called the "Push." When he becomes a father, his world shifts dramatically, forcing him to confront his past and attempt to escape the violent, impoverished life he's always known. Stone's work captures a neglected phase of Australian society with humor, observation, and unexpected kindness, painting an unflinching portrait of slum life and the possibility of redemption. (This is an automatically generated summary.)
Wikipedia page about this book: https://en.wikipedia.org/wiki/Jonah_(novel)
Release date is 2003-01-01
Produced by Col Choat. HTML version by Al Haines.
Keywords: Australia -- Fiction